Synthesis and bioactivity of pyrrole-conjugated phosphopeptides - Zhang, Qiuxin; Tan, Weiyi; Xu, Bing (Beilstein Journal of Organic Chemistry, 2022)
Here we report the synthesis and effect on the cell viability of pyrrole-conjugated phosphopeptides. Encouraged by the selective inhibition of cancer cells by a naphthyl-capped phosphopeptide (Nap-ffpy, 1), we conjugated the heteroaromatic dipyrrole or tripyrrole motif at the N-terminal of short peptides containing phosphotyrosine or phosphoserine and examined the bioactivity of the resulting phosphopeptides (2–10). Although most of the phosphopeptides exhibit comparable activities with that of 1 against HeLa cells at 200 μM, they, differing from 1, are largely compatible with HeLa cells at 400 μM. Enzymatic dephosphorylation of 2–10, at 400 μM is unable to induce a dramatic morphological transition of the peptide assemblies observed in the case of 1. These results suggest that a heteroaromatic motif at the N-terminal of peptides likely disfavors the formation of extensive nanofibers or morphological changes during enzymatic self-assembly, thus provide useful insights for the development of phosphopeptides as substrates of phosphatases for controlling cell fate.
Keywords: cells; enzyme; N-terminal; peptides; pyrroles; self-assembly